(untitled) (Research, Society and Development, 2026)
Mangrove ecosystems are highly productive coastal environments increasingly threatened by biological invasions, which can alter community structure and ecosystem functioning. The invasive bivalve Isognomon bicolor (C. B. Adams, 1845), native to the Caribbean, has expanded along the Brazilian coast; however, its ecological dynamics in non-conventional mangrove systems remain poorly understood. This study evaluates the population structure of I. bicolor in the Mangue de Pedra, a unique groundwater-influenced rocky mangrove located in Armação dos Búzios (Rio de Janeiro, Brazil). A quantitative sampling design was applied using 30 quadrats (0.09 m² each) distributed across three microhabitats: roots/muddy substrate, rocky talus, and consolidated rocky shore. A total of 1,351 individuals were recorded, with 100% occurrence across all sampled quadrats, indicating widespread distribution at the local scale. However, abundance varied markedly among habitats, with higher densities in consolidated substrates (1120.0 ind m⁻²), intermediate values in rocky talus (312.2 ind m⁻²), and lower densities in muddy root-associated environments (68.9 ind m⁻²). This pattern demonstrates a clear decoupling between occurrence and abundance, indicating that while dispersal facilitates broad colonization, local environmental filtering, particularly substrate stability, plays a key role in regulating population density. The structural heterogeneity and hydrological connectivity of the Mangue de Pedra suggest that this system may function both as a recipient environment and as a potential source of propagules.